Pengaruh Kecukupan Modal, Risiko Kredit t/erhadap Profitabilitas dengan Efisiensi sebagai Variabel Intervening - Anugrah Sepnu Utama; Risal Rinofah; Pristin Prima Sari (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to determine whether there is an effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL) on Profitability (ROA) with Efficiency (BOPO) as an Intervening Variable, in conventional commercial banks in Indonesia listed on the Indonesia Stock Exchange period (2016). -2020). Sampling using the purposive sampling method with the criteria that the bank has a complete published report in 2016-2020, and the bank has a non-negative ROA. This study uses data obtained from the bank's Annual Financial Statements issued by the bank in the Financial Services Authority (OJK) Bank Published Financial Statements. The analytical technique used is a statistical test through the Ttest, Ftest, R2, Multiple Regression Test, and Sobel Test using the Sobel Test Calculator for the Significance of Mediation. The results of the analysis on the t test show that CAR has a negative and insignificant effect on ROA, NPL has a negative and insignificant effect on ROA, BOPO has a negative and significant effect on ROA. CAR has a negative and significant effect on BOPO, NPL has no significant effect on BOPO. And the results of the Sobel test showed that BOPO was able to mediate the CAR variable on ROA but was unable to mediate the effect of NPL on ROA. Keywords: CAR; NPL; ROA; BOPO